The Psychological Impact of COVID-19 on Individuals With and Without Mental Health Disorders - Campos, Juliana Alvares Duarte Bonini [UNESP]; Campos, Lucas Arrais [UNESP]; Martins, Bianca Gonzalez [UNESP]; Valadão Dias, Filomena; Ruano, Rodrigo; Maroco, João (SAGE Publications, 2021)
Objective: To identify people with history of mental health disorders before the COVID-19 pandemic in the Brazilian population and estimate the prevalence of mood swings and the subjective distress of the pandemic among individuals with or without mental health disorders. Methods: Through an online survey, participants were asked about presence or absence of mental health disorders. In addition, they answered the Brunel Mood Scale and the Impact of Event Scale. The mean percentile of mood swing indicators and psychological impact scores were estimated, and data were analyzed by logistic regression. Results: 13,248 people participated (70.5% women, mean age 35.4 years, 31.2% with history of mental health disorder). Women and younger people were more likely to be diagnosed with mental health disorder. All participants had significant changes in mood due to the pandemic. Anger, depressed mood, mental confusion, and fatigue were higher among individuals with bipolar disorder or with combined disorders. Individuals with mental health disorders had a greater subjective distress, especially the group with bipolar disorder (OR = 4.89 [3.64–6.56]) and combined disorders (OR = 6.89 [5.21–9.10]). Conclusion: Individuals previously diagnosed with mental health disorders at some point in life are more vulnerable to psychological impact from the pandemic.
Keywords: COVID-19; mental disorders; Mental health; pandemics